Layering of magnetic nanoparticles at amorphous magnetic templates with perpendicular anisotropy. Issue 33 (17th August 2020) - Saini, Apurve; Borchers, Julie A.; George, Sebastian; Maranville, Brian B.; Krycka, Kathryn L.; Dura, Joseph A.; Theis-Bröhl, Katharina; Wolff, Max
Abstract : We reveal the assembly of magnetite nanoparticles of sizes 5 nm, 15 nm and 25 nm from dilute water-based ferrofluids onto an amorphous magnetic template with out-of-plane anisotropy. Abstract : We reveal the assembly of magnetite nanoparticles of sizes 5 nm, 15 nm and 25 nm from dilute water-based ferrofluids onto an amorphous magnetic template with out-of-plane anisotropy. From neutron reflectometry experiments we extract density profiles and show that the particles self-assemble into layers at the magnetic surface. The layers are extremely stable against cleaning and rinsing of the substrate. The density of the layers is determined by and increases with the remanent magnetic moment of the particles.